Downregulation of MerTK in circulating T cells of patients with non-proliferative diabetic retinopathy - Bu, Shimiao; Ling, Jiang-Yue; Wu, Xiaojun; Zhang, Liting; Shi, Xiangyu; Huang, Lang; Zhao, Zheng; Yang, Ying; Xiang, Zongqin; Liu, Yong U.; Liu, Yufeng; Zhang, Yuehong (Frontiers in Endocrinology, 2025)
ObjectiveTo explore the differential gene expression in peripheral blood immune cells of individuals with type 2 diabetes mellitus (DM), comparing those with and without non-proliferative diabetic retinopathy (NPDR).MethodsFrom a pool of 126 potential participants, 60 were selected for detailed analysis. This group included 12 healthy donors (HDs), 22 individuals with DM, and 26 with NPDR. We analyzed peripheral blood mononuclear cells (PBMCs) using RNA sequencing and quantitative PCR (qPCR) to pinpoint differentially expressed genes (DEGs). Western blot and flow cytometry were also employed to evaluate the protein expression of specific genes.ResultsIn patients with NPDR compared to those with DM alone, MerTK—a gene implicated in inherited retinal dystrophies due to its mutations—was notably downregulated in PBMCs. Through flow cytometry, we assessed the protein levels and cellular distribution of MerTK, finding a predominant expression in monocytes and myeloid-derived suppressor cells (MDSCs), with a marked reduction in CD4+ and CD8+ T cells, as well as in natural killer T (NKT) cells. Patients with DM demonstrated a significant deviation in the PBMCs composition, particularly in B cells, CD4+ T cells, and NK cells, when compared to HDs. ConclusionsThe study indicates that MerTK expression in T cells within PBMCs could act as a viable blood biomarker for NPDR risk in patients with DM. Furthermore, the regulation of T cells by MerTK might represent a critical pathway through which DM evolves into NPDR.